Impact of the preparation method of red cell concentrates on transfusion indices in thalassemia patients: A randomized crossover clinical trial. Issue 6 (4th May 2021) - Gamberini, Maria Rita; Fortini, Monica; Stievano, Alice; Calori, Eleonora; Riontino, Maria Vittoria; Ceccherelli, Giovanni; Venturelli, Donatella; Chicchi, Roberta; Biguzzi, Rino; Fagnoni, Francesco; Portararo, Giuseppina Angela; Lasagni, Daniela; et al.
Abstract: Background: The average hemoglobin content of red cell concentrates (RCC) varies depending on the method of preparation. Surprisingly less data are available concerning the clinical impact of those differences. Study Design and Methods: The effects of two types of RCC (RCC‐A, RCC‐B) on transfusion regime were compared in a non‐blinded, prospective, randomized, two‐period, and crossover clinical trial. RCC‐A was obtained by whole blood leukoreduction and subsequent plasma removal, RCC‐B removing plasma and buffy coat first, followed by leukoreduction. Eligible patients were adult, with transfusion‐dependent thalassemia (TDT). Results: RCC‐A contained 63.9 (60.3–67.8) grams of hemoglobin per unit (median with 1 st and 3 rd quartile), RCC‐B 54.5 (51.0–58.2) g/unit. Fifty‐one patients completed the study. With RCC‐B, the average pre‐transfusion hemoglobin concentration was 9.3 ± 0.5 g/dl (mean ± SD), the average transfusion interval 14.2 (13.7–16.3) days, the number of RCC units transfused per year 39.3 (35.4–47.3), and the transfusion power index (a composite index) 258 ± 49. With RCC‐A, the average pre‐transfusion hemoglobin concentration was 9.6 ± 0.5 g/dl (+2.7%, effect size 0.792), the average transfusion interval 14.8 (14.0–18.5) days (+4.1%, effect size 0.800), the number of RCC units transfused per year 34.8 (32.1–42.5) (−11.4%, effect size −1.609), and the transfusion power index 272 ± 61 (+14.1%, effect size 0.997). All differences were statistically highly significant ( p  < .00001). The frequency of transfusion reactions was 0.59% with RCC‐A and 0.56% with RCC‐B ( p  = 1.000). Conclusion: To reduce the number of RCC units consumed per year and the number of transfusion episodes, TDT patients should receive RCC with the highest average hemoglobin content.